Effectiveness of BUSUU Application Improving Speaking Skills Students at The Al-Mahira Islamic International Boarding School - Salamah, Ummu; Ulum, Samsul; Sutaman, Sutaman (STIQ Amuntai, 2025)
Appropriate teaching tools, students' proficiency, and students' lack of confidence. These problems occurred at Al-Mahara Islamic International School in Malang. Therefore, through this research, the researcher aims to offer a solution to these problems by applying the Busuu application to improve speaking skills for seventh-grade students at Al-Mahara Islamic International School in Malang. The hypothesis of this study is that the use of the Busuu application to enhance speaking skills is effective. This research employs a quantitative, descriptive, pre-experimental design using pre-test and post-test formats. The research variables include independent and dependent variables. The average pre-test score was 72.60, and the average post-test score was 80.80. Comparing the pre-test and post-test values, the t-value was 4.459, and the significance value (2-tailed) was 0.000, indicating a significant difference between the pre-test and post-test results. The t-value (4.459) exceeded the t-table value (2.093). This indicates that the hypothesis of this research, Ha, is accepted, and Ho is rejected, meaning that the application of the Busuu application is effective in improving speaking skills for seventh-grade students at Al-Mahara Islamic International School in Malang.